2010
DOI: 10.1111/j.1469-0691.2010.03165.x
|View full text |Cite
|
Sign up to set email alerts
|

Tn5090-like class 1 integron carrying blaVIM-2 in a Pseudomonas putida strain from Portugal

Abstract: Three Pseudomonas putida strains containing bla(VIM-2) were isolated from an inanimate surface of a female ward sanitary facility in the Hospital Infante D. Pedro, Aveiro. A novel class 1 integron was found in strain Pp2 (aacA4/bla(VIM-2)/aac6'-IIc disrupted by an insertion sequence IS1382), and strain Pp1 was found to carry a class 1 integron (aacA7/bla(VIM-2)/aacC1/aacA4), which is described for the first time in this species. Strain PF1 carries a class 1 integron associated with a Tn5090-like transposon, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…This gene arrangement, in combination with intl1, is involved in the transfer of a bla VIM-2 -carrying cassette in clinical Pseudomonas spp. (16)(17)(18)(19). A 9,875-bp fragment containing the bla VIM-2 -like gene was observed in three P. putida strains that shared 99.9% sequence identity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This gene arrangement, in combination with intl1, is involved in the transfer of a bla VIM-2 -carrying cassette in clinical Pseudomonas spp. (16)(17)(18)(19). A 9,875-bp fragment containing the bla VIM-2 -like gene was observed in three P. putida strains that shared 99.9% sequence identity.…”
mentioning
confidence: 99%
“…Similar to the spread of bla VIM-2 in bacteria of clinical origin, the mobile genetic elements, such as Tn5090, Tn1403, intl1, and IS6100, may play an important role in the dissemination of the bla VIM gene and its conserved flanking regions in bacteria among food animals (16,17,24). Our study has found MBL-producing Pseudomonas isolates not only in the livestock but also in their surrounding environment, suggesting that surveillance of carbapenemase-producing bacteria in livestock and their surrounding environment is urgently needed.…”
mentioning
confidence: 99%
“…Several studies have described class 1 integrons containing the bla VIM-2 gene cassette (Walsh et al, 2005;Santos et al, 2010;Samuelsen et al, 2010;Hammami et al, 2010), but to our knowledge, this is the first report of the double detection of bla VIM-2 gene cassettes in the variable region of the same integron in P. aeruginosa. In addition, the presence of a new insertion sequence in the surrounding environment could be implicated in the mobilization of these gene cassettes.…”
Section: Jmm Correspondencementioning
confidence: 86%
“…The bla VIM-2 gene has been commonly associated with chromosomally located Tn402-like class 1 integrons (3)(4)(5)(6)(7)(8). This gene also has been less frequently linked to plasmids, usually smaller than 100 kb, and cannot be transferred by conjugation, at least not to Escherichia coli (1,9).…”
mentioning
confidence: 99%
“…In P. aeruginosa, bla VIM-2 is most often associated with class 1 integrons containing additional antibiotic resistance genes (3)(4)(5)(6)(7)(8)(9)(10)(11). The bla VIM-2 gene has been commonly associated with chromosomally located Tn402-like class 1 integrons (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%